2020
DOI: 10.1111/apa.15585
|View full text |Cite
|
Sign up to set email alerts
|

A randomised crossover trial of closed loop automated oxygen control in preterm, ventilated infants

Abstract: Aim To determine whether closed loop automated oxygen control resulted in a reduction in the duration and severity of desaturation episodes and the number of blood gases and chest radiographs in preterm, ventilated infants. Methods Infants were studied on two consecutive days for 12 hours on each day. They were randomised to receive standard care (standard period) or standard care with a closed loop automated oxygen control system (automated oxygen control period) first. Results Twenty‐four infants with a medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 24 publications
1
20
0
1
Order By: Relevance
“…Compared with the TR time of 80% in this study, other studies of OxyGenie control have demonstrated TR times of 81% 23 and 88%. 28 For CLiO 2 (69% TR time in this study), other studies have shown TR time of 40%, 15 58%, 16 62%, 18 76%, 19 73% 20 and 62% 24 ).…”
Section: Discussionsupporting
confidence: 49%
“…Compared with the TR time of 80% in this study, other studies of OxyGenie control have demonstrated TR times of 81% 23 and 88%. 28 For CLiO 2 (69% TR time in this study), other studies have shown TR time of 40%, 15 58%, 16 62%, 18 76%, 19 73% 20 and 62% 24 ).…”
Section: Discussionsupporting
confidence: 49%
“…Closed loop automated oxygen control systems have yet to be trialled in infants with CDH, but recent developments have shown promising results in optimising ventilatory support in other pulmonary conditions (52)(53)(54)(55)(56). Whether such a modality has a role in infants with congenital diaphragmatic anomalies has yet to be determined.…”
Section: Closed Loop Automated Oxygen Controlmentioning
confidence: 99%
“…As a matter of fact, as documented in a recent randomized crossover trial in preterm infants, the utilization of automated oxygen controllers in ventilated infants resulted in significantly fewer desaturations lasting > 30 s and more time spent in the SpO 2 target range. However, there was no significant effect on the quantity of blood gases, or the number of chest radiographs obtained [37]. In a retrospective cohort study in which clinical outcomes of preterm infants were evaluated before and after the implementation of automated oxygen control as the standard of care, invasive ventilation was significantly shorter in infants who received automated oxygen control.…”
Section: Oxygen Therapy: Saturation Targets and Automated Controlmentioning
confidence: 94%
“…Given the direct association of IMV with organ damage, especially in the immature neonatal lung, research along with technological advances in the field of neonatal ventilators allowed for progression toward the introduction of new concepts and the implementation of new ventilatory techniques (Table 1). [ [33][34][35] HFV + VG Unknown [36,37] Non-Invasive Ventilation (NIV) modes nCPAP Reduced BPD at 36 wks, death or BPD. [38,39] Bi-level NIV nIPPV Reduced risk of respiratory failure and intubation.…”
Section: Most Important Developments In Imv and Their Effect On Outcomesmentioning
confidence: 99%